2023
DOI: 10.1177/10398562231167681
|View full text |Cite
|
Sign up to set email alerts
|

Characterising variability in youth mental health service populations: A detailed and scalable approach using digital technology

Abstract: Objective This study utilised digital technology to assess the clinical needs of young people presenting for care at headspace centres across Australia. Method 1490 young people (12–25 years) who presented to one of 11 headspace services from four geographical locations (urban New South Wales, urban South Australia, regional New South Wales, and regional Queensland) completed a digital multidimensional assessment at initial presentation. Characteristics were compared between services and geographical locations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Their work highlights the potential of digital MH services when assessment, triage, and care pathways are created to ensure that young people are matched to the care they need [ 15 ]. More recently, the Innowell eMH platform has been used to compare the needs of clients among services and across geographic regions, which can be used to understand the needs of a heterogeneous population and plan services accordingly [ 80 ]. This highlights the potential of eMH tools to ensure that youth are accessing the right care at the right time and promoting the continuity of care to avoid the fragmentation of services [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their work highlights the potential of digital MH services when assessment, triage, and care pathways are created to ensure that young people are matched to the care they need [ 15 ]. More recently, the Innowell eMH platform has been used to compare the needs of clients among services and across geographic regions, which can be used to understand the needs of a heterogeneous population and plan services accordingly [ 80 ]. This highlights the potential of eMH tools to ensure that youth are accessing the right care at the right time and promoting the continuity of care to avoid the fragmentation of services [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further to this are the potential effects of functional impairment on PLEs which were also observed in these networks. This is critical given the increased rate of PLEs in those presenting to youth mental health services and the future risks they confer (Capon et al, 2023;Yung et al, 2008). Previous research has shown the importance of the direct impacts of improving social and occupational functioning through individual placement support (Heffernan & Pilkington, 2011;Killackey et al, 2008;Michon et al, 2014); however, indirect effects of these interventions could be expected on suicide ideation and self-harm (McGorry et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This is critical given the increased rate of PLEs in those presenting to youth mental health services and the future risks they confer (Capon et al. , 2023 ; Yung et al. , 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Innowell Platform is an online platform that aims to assist the assessment, management, and monitoring of mental ill health and maintenance of well-being 3,52 . It is a Web-based platform that can be accessed via traditional computing and mobile devices.…”
Section: The Innowell Platformmentioning
confidence: 99%